Time varying mesh stiffness calculation of spur gear pair considering sliding friction and spalling defects. (December 2016) - Saxena, Ankur; Parey, Anand; Chouksey, Manoj
Abstract: Spalling is one of the common tooth surface failures of gear teeth and is defined as the formation of deeper cavities that are mainly developed from subsurface defects. The time varying mesh stiffness (TVMS) of gear pairs, gives significant information about the health of the system. The change indirection of time varying friction on both sides of the pitch line causes the change of gear mesh stiffness. This article proposes a computer simulation based approach to study the effect of time varying friction coefficient on the total effective mesh stiffness for the spur gear pair. An analytical method to calculate the TVMS of the spur gear for different spall shapes, size and location considering sliding friction is also proposed in this study. The results show that spall shape, size and location are very important parameters that need to be considered for calculation of TVMS and subsequently to know the dynamic response of the gear pair in the presence of a spall. Highlights: Time varying mesh stiffness for different spall shape, size and location. Modified analytical method for calculation of time varying mesh stiffness. Effect of varying friction coefficient on time varying mesh stiffness in presence of spall.